Plastid Ultrastructure, Chlorophyll Contents and Colour Expression during Ripening of Cavendish Banana (Musa Acuminata ‘Willams at 18°C and 27°C - Ding, Phebe; Ahmad, Siti Hajar; Abd. Razak, Abd. R.; Tengku Muda Mohamed, Mahmud; Saari, Nazamid (2007)
When Cavendish banana (Musa acuminata ‘ William ‘) is ripened at tropical ambient temperature (27°C ) the peel fails to degreen although the pulp has softened . However , the peel will degreen to a yellow colour when the fruit is ripened at 18°C .The inability of the peel to degreen could be because of the retention of thylakoid membranes in the plastids and chlorophyll during the ripening process.A study was carried out to investigate the relationships between plastid ultrastructure , chlorophyll content , and peel colour of Cavendish banana ripened at 18±2°C (C18) and 27 ±2°C (27) . The peel of Cavendish banana underwent complete degreening when the fruit was ripened at a temperature of 18 °C to produce a yellow fruit at ripening stage (RS)6 , after 9 days of treatment. In contrast , bananas exposed to 27°C failed to degreen . By day 5 after ripening initiation , the pulp had softened to eating ripe in those fruit and brown specks appeared on the fruit peel indicating that senescence had begun . Transmission electron microscopy revealed that the grana-thylakoid membranes of peel chromoplasts had iysed by RS 6 in C18 fruit and only 40% of the total chlorophyll content from RS1 was retained . In contrast ,the grana –thylakoid membranes in C27 at day 5 were retained , along with retention of 57% of total chlorophyll content . Total chlorophyll content of C27 fruit correlated significantly with L* , C * and h ° colour values . The higher percentage of total chlorophyll retained in C27 compared with C18 fruit did not fully unmask the existing peel carotenoids thus producing a pale-green fruit .